Efficiency of biofloc application on growth, survival rate and water quality change in intensive hybrid catfish culture in indoor pond - Is-haak, Jesada; Kijjabandhit, Thanit; Koydon, Supavadee; Ngamphongsai, Chansawang; Prasertkulsak, Sirilak; Sinpho, Phitsanu (RMUTSB ACADEMIC JOURNAL, 2024)
The efficiency of biofloc application in intensive hybrid catfish culture in indoor ponds, compared to the control group without biofloc adding, was investigated. The experimental units were 6 of 3-meter-diameter PE rounded ponds, with 75 cm depth and 5.30 m3 of water volume. The experimental fish, with initial average weight and length of 1.24+0.09 g and 5.03+0.07 cm, respectively, were stocked at the stocking density of 1500 fish per pond. The experimental feed was commercial floating pellet. The trial was conducted for 17 weeks. The data of growth performance and survival rate of fish were recorded, including the water quality in experimental ponds. At the end of the experiment, it was found that average weight, average weight gain, daily weight gain and survival rate of fish in biofloc treatment, which were 188.90+4.67 and 168.40+3.82 g, 187.65+4.60 and 167.17+3.71 g, 1.58+0.06 and 1.41+0.04 g/day and 95.00+1.73 and 85.00+0.00%, respectively, were significantly higher than those of the control group (P<0.05). On the other hand, the FCR and feeding cost of 1 kg of fish, which were 1.33+0.04 and 1.50+0.19, and 33.08+0.12 and 36.38+1.05 Baht per kg, respectively, were significantly lower than those of the control group (P<0.05). The feed cost could be reduced by 3.30 baht per 1 kg of fish. Water qualities, throughout the experimental period, were in the optimal range for hybrid catfish growth. Biofloc application data had high negative Pearson's correlation coefficients to the ammonia (r=-0.89**) and also moderate positive correlation coefficients to phosphorus (r=0.57*).